1994
DOI: 10.1111/j.1365-2273.1994.tb01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting resolution of otitis media with effusion in children

Abstract: There is only limited knowledge of the factors which influence the outcome of otitis media with effusion in children in the long-term. This randomized controlled study assessed the therapeutic effect of adenoidectomy and adenotonsillectomy during a 5-year follow-up. Numerous pre-treatment independent variables concerning the child's upper and lower respiratory tract, atopic status and parental habits were assessed in relation to two dependent outcome measures. These were otoscopic clearance of effusion and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…We also know that breast-feeding plays an important role in craniofacial development and growth and also in the development of oro-facial muscles [22,23]. But we did not found association between otitis and breast-…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We also know that breast-feeding plays an important role in craniofacial development and growth and also in the development of oro-facial muscles [22,23]. But we did not found association between otitis and breast-…”
Section: Discussionmentioning
confidence: 95%
“…A shorter vertical dimension of the face may imply in a poorer Eustachian tube dysfunction. Maw and Bawden [22] suggested that children with serous otitis media have experienced delayed craniofacial growth. Shibahara and Sando [30] describe that the insertion angle of these muscles may alter the vectors of traction in the opening of the tube.…”
mentioning
confidence: 99%
“…Previous studies with recurrent AOM or MEE as outcomes have identified different variables with impact on the diseases, e.g. type of day care [7,26] parental smoking [11,27], duration of breastfeeding [8,9,28] and socioeconomic factors [7,8]. To our knowledge no other studies have analyzed the extent to which symptoms at inclusion are associated with the short-term course of OM.…”
Section: Explanations and Comparison With Other Studiesmentioning
confidence: 99%
“…Adenoidectomy has been shown to be effective in improving the resolution rate of OME, 159–164 but whether this is because it removes a physical obstruction of the eustachian tube, or a source of ascending infection is a matter for debate. The presence of laterally placed adenoid tissue around the torus tubarius is associated with OME, 165 but the absolute size of the adenoids is not.…”
Section: Why Is the Effusion Not Cleared Effectively?mentioning
confidence: 99%